'Modulation' by Richard Powers: Digital sound, compression and the short story. Issue 1 (1st June 2021) - Hedges, Michael
This article presents a reading of 'Modulation' (2008) by Richard Powers. Firstly, I consider the short story's representation of the MP3 music file, specifically its effects on how music is circulated and stored, as well as how it sounds. These changes are the result of different processes of compression. The MP3 format makes use of data compression to reduce the file size of a digital recording significantly. Such a loss of information devises new social and material relations between what remains of the original music, the recording industry from which MP3s emerged and the online markets into which they enter. I argue that 'Modulation' is a powerful evocation of a watershed moment in how we consume digital sound: what Jonathan Sterne has termed the rise of the MP3 as 'cultural artifact'. I contend that the short story, like the MP3, is also a compressed manner of representation. I use narrative theory and short story criticism to substantiate this claim, before positioning 'Modulation' alongside Powers's novels of information. I conclude by suggesting that 'Modulation' offers an alternative to representing information through an excess of data. This article reads Powers's compressed prose as a formal iteration of the data compression the story narrates.